2013
DOI: 10.1124/mol.113.085100
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Fucoidan Improves Endoplasmic Reticulum Stress-Reduced Insulin Sensitivity through AMP-Activated Protein Kinase Activation in L6 Myotubes and Restores Lipid Homeostasis in a Mouse Model of Type 2 Diabetes

Abstract: Low molecular weight fucoidan (LMWF) is widely used to treat metabolic disorders, but its physiologic effects have not been well determined. In the present study, we investigated the metabolic effects of LMWF in obese diabetic mice (leptin receptor-deficient db/db mice) and the underlying molecular mechanisms involved in endoplasmic reticulum (ER) stressresponsive L6 myotubes. The effect of LMWF-mediated AMP-activated protein kinase (AMPK) activation on insulin resistance via regulation of the ER stress-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 57 publications
4
41
0
Order By: Relevance
“…In addition, Jeong et al found that LMWF improves insulin sensitivity through AMPK activation and restores lipid homeostasis in a mouse model of type 2 diabetes. 48 Thus, this may be one of the mechanisms that explain its activation of eNOS phosphorylation; however, further and more detailed studies are necessary regarding how LMWF improves endothelial dysfunction in diabetes. In addition, it appears that LMWF demonstrated a dosedependent but not proportional effect on endothelium damage in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Jeong et al found that LMWF improves insulin sensitivity through AMPK activation and restores lipid homeostasis in a mouse model of type 2 diabetes. 48 Thus, this may be one of the mechanisms that explain its activation of eNOS phosphorylation; however, further and more detailed studies are necessary regarding how LMWF improves endothelial dysfunction in diabetes. In addition, it appears that LMWF demonstrated a dosedependent but not proportional effect on endothelium damage in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Blood glucose levels of all mice were measured with Glucostix AccuCheck (Roche Diagnostics, Mannheim, Germany), and blood ethanol levels were quantified with Ethanol assay kit (Sigma-Aldrich). Serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and cholesterol were determined with an automated blood analyzer (AU400; Olympus, Tokyo, Japan) [21]. Total adiponectin levels were measured using a commercial ELISA kit from R&D Systems (Minnesotapolis, MN, USA), and insulin levels were analyzed with the insulin enzyme-linked immunosorbent assay test kit (Mercodia, Uppsala, Sweden).…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…Hepatic and serum bile acid (BA) were measured with Bile acid L3K assay kit (Cell Biolabs, Inc., San Diego, CA, USA). Serum cytokine concentrations were measured using a BD Cytometry Bead Array (BD Bioscience, San Jose, CA, USA) in accordance with the manufacturer's instructions, as described previously [21].…”
Section: Biochemical Assaysmentioning
confidence: 99%
See 2 more Smart Citations